O enigma do espaço-tempo : considerações sobre a relação material entre a aceleração do mundo e a pós-modernidade - Alves, Victor Hugo Andrade (2019)
This work consists in demonstrate the material relation to the acceleration of the world and the condition of post-modernity. The acceleration of the world happens with the phenomena of the space-time compression, with this being generated on behalf of the technological transformations which ends up creating possible material conditions for construction of communications and transport systems in a global leve at a speed never seen before. This process generates deep effects in the sense which men perceive the world and space-time. Post-modernity is a condition which the ephemeral, the chaotic and the historically discontinuous become dominant on the social relations and the way it sees the world – there is no more metarratives that we can follow anymore, neither we have a final goal which gaves sense to this state of eternal change. To mankind, the only option which remained is to enjoy the continuous present condition which the postmodern world offers, reinforcing its plurality and difference against ideias such as uniformity, any kind of teleology and even history itself. The problem that our research sought out to answer was: What's the relation between the time-space and post-modernity? What are the convergences? The theoretical method used was geographical-historical- materialism, with it being necessary not only taking into account the time question, but space as well, to get to historical and geographical truths, as David Harvey said. Posteriorly, based on the development of the three topics, we sought to incorporate the thesis which the material condition is dominant (at first instance) for the production of meaning which man and his society has about space-time. This was a theoretical research, based on bibliographic research. Our conclusion is that the change in the character of capitalist accumulation, from fordism to flexible (starting with the process of liberation of capital to dominate the globe) transformed the meaning of space-time to man, generating in the superstructure the condition of ephemerality, fragmentation and instability which the condition of post-modernity is formed.